(untitled) (Eurasian Medical Research Periodical, 2023)
Ferroptosis is a recently identified type of regulated cell death. Specifically, it is a nonapoptotic, iron-dependent, oxidative cell death mechanism that was proposed by Dixon. There are several prospects regarding ferroptosis in the nervous system. Importantly, there is a need for chemical probes or biomarkers capable of elucidating the ferroptosis mechanism to determine its role in the nervous system given the quick cell death occurrence and difficulty in obtaining appropriate neurons. This review would aim to highlighting the role of free iron, their transported such divalent metal transporter 1 (DMT1) and ferritin in Neurodegeneration disease